A multi-faceted comparative perspective on elevational beta-diversity: the patterns and their causes. Issue 1949 (21st April 2021) - Du, Yuanbao; Fan, Liqing; Xu, Zhenghui; Wen, Zhixin; Cai, Tianlong; Feijo, Anderson; Hu, Junhua; Lei, Fumin; Yang, Qisen; Qiao, Huijie
Abstract : The observed patterns and underlying mechanisms of elevational beta-diversity have been explored intensively, but multi-dimensional comparative studies remain scarce. Herein, across distinct beta-diversity components, dimensions and species groups, we designed a multi-faceted comparative framework aiming to reveal the general rules in the observed patterns and underlying causes of elevational beta-diversity. We have found that: first, the turnover process dominated altitudinal patterns of species beta-diversity ( β sim > β sne ), whereas the nestedness process appeared relatively more important for elevational trait dissimilarity ( β funcsim < β funcsne ); second, the taxonomic turnover was relative higher than its phylogenetic and functional analogues ( β sim > β phylosim / β funcsim ), conversely, nestedness-resultant trait dissimilarity tended to be higher than the taxonomic and phylogenetic measures ( β funcsne > β sne / β phylosne ); and third, as elevational distance increased, the contradicting dynamics of environmental filtering and limiting similarity have jointly led the elevational patterns of beta-diversity, especially at taxonomic dimension. Based on these findings, we infer that the species turnover among phylogenetic relatives sharing similar functional attributes appears to be the main cause of shaping the altitudinal patterns of multi-dimensional beta-diversity. Owing to the methodological limitation in the randomization approach, currently, it remains extremely challenging to distinguish the influence of the neutral process from the offset between opposing niche-based processes. Despite the complexities and uncertainties during species assembling, with a multi-dimensional comparative perspective, this work offers us several important commonalities of elevational beta-diversity dynamics.